Dancing with the devil: Intervention programs under criminal governance in Northern Central America - Rosen, Jonathan D. (Criminology & criminal justice, 2025)
This article examines how violence intervention programs are implemented in places governed by street gangs. It is based on focus groups conducted in communities impacted by gangs and gang-related violence in the countries of Northern Central America. We develop a typology for understanding the different mechanisms for interacting with gangs. In places where gangs rule, it is not possible for non-governmental workers to avoid gangs. Instead, we argue that community workers implementing programs in gang neighborhoods are required to acknowledge the power and presence of gangs and readapt their strategies to carry on implementing the programs.